Implementation of molecular karyotyping in clinical genetics - Luca Lovrecic; Borut Peterlin (Zdravniški Vestnik, 2013)
Rapid development of technologies for the study of the human genome is an expected step after the discovery and sequencing of the entire human genome. Chromosomal microarrays, which allow us to perform tens of thousands of previously individual experiments simultaneously, are being utilized in all areas of human genetics and genomics. Initially, this was applicable only for research purposes, but in the last few years their clinical diagnostic purposes are becoming more and more relevant. Using molecular karyotyping (also chromosomal microarray, comparative genomic hybridization with microarray, aCGH), one can analyze microdeletions / microduplications in the whole human genome at once. It is a first-tier cytogenetic diagnostic test instead of G-banded karyotyping in patients with developmental delay and/or congenital anomalies. Molecular karyotyping is used as a diagnostic test in patients with unexplained developmental delay and/or idiopathic intellectual disability and/or dysmorphic features and/or multiple congenital anomalies (DD/ID/DF/MCA). In addition, the method is used in prenatal diagnostics and in some centres also in preimplantation genetic diagnosis. The aim of this paper is to inform the professional community in the field about this new diagnostic method and its implementation in Slovenia, and to define the clinical situations where the method is appropriate.